Low Dose X-Ray Sources and High Quantum Efficiency Sensors: The Next Challenge in Dental Digital Imaging? - Arnav R. Mistry; Daniel Uzbelger Feldman; Jie Yang; Eric Ryterski (Radiology Research and Practice)
Objective(s). The major challenge encountered to decrease the milliamperes (mA) level in X-ray imaging systems is the quantum noise phenomena. This investigation evaluated dose exposure and image resolution of a low dose X-ray imaging (LDXI) prototype comprising a low mA X-ray source and a novel microlens-based sensor relative to current imaging technologies. Study Design. A LDXI in static (group 1) and dynamic (group 2) modes was compared to medical fluoroscopy (group 3), digital intraoral radiography (group 4), and CBCT scan (group 5) using a dental phantom. Results. The Mann-Whitney test showed no statistical significance (α=0.01) in dose exposure between groups 1 and 3 and 1 and 4 and timing exposure (seconds) between groups 1 and 5 and 2 and 3. Image resolution test showed group 1 > group 4 > group 2 > group 3 > group 5. Conclusions. The LDXI proved the concept for obtaining a high definition image resolution for static and dynamic radiography at lower or similar dose exposure and smaller pixel size, respectively, when compared to current imaging technologies. Lower mA at the X-ray source and high QE at the detector level principles with microlens could be applied to current imaging technologies to considerably reduce dose exposure without compromising image resolution in the near future.